Visualization and analysis of lipopolysaccharide distribution in binary phospholipid bilayers - Henning, María Florencia (2009)
Lipopolysaccharide (LPS) is an endotoxin released from the outer membrane of Gram-negative bacteria during infections. It have been reported that LPS may play a role in the outer membrane of bacteria similar to that of cholesterol in eukaryotic plasma membranes. In this article we compare the effect of introducing LPS or cholesterol in liposomes made of dipalmitoylphosphatidylcholine/dioleoylphosphatidylcholine on the solubilization process by Triton X-100. The results show that liposomes containing LPS or cholesterol are more resistant to solubilization by Triton X-100 than the binary phospholipid mixtures at 4 °C. The LPS distribution was analyzed on GUVs of DPPC:DOPC using FITC-LPS. Solid and liquid-crystalline domains were visualized labeling the GUVs with LAURDAN and GP images were acquired using a two-photon microscope. The images show a selective distribution of LPS in gel domains. Our results support the hypothesis that LPS could aggregate and concentrate selectively in biological membranes providing a mechanism to bring together several components of the LPS-sensing machinery.